Dark web and bitcoin: an analysis of the impact of digital anonymate and criptomoids in the practice of money laundering crime - Palitot Braga, Romulo Rhemo; Barbosa Luna, Arthur Augusto (Direito e Desenvolvimento, 2018)
This article analyzes some of the existing digital anonymity technologies, as well as their impact on the process and facilitation of the money laundering process. It presents the concept of superficial Internet and clarifies the difference between the Deep Web and the Dark Web, exposing how it works one of its most important operating structures, the TOR protocol. It also details the operation of BitCoin, one of the most important crypto-coins today, and draws a parallel on how these technologies can impact the practice of money laundering, as well as discusses the capacity of the mechanisms currently in place to curb and punish it. The anonymity guaranteed by the use of BitCoin is so much that in the first half of May 2017, hackers infected thousands of computers in dozens of countries, including Brazil, the United Kingdom, the United States, China, Russia, Spain and Italy, encrypting computer files and requiring redemption payment for the coded data.